AuS-ConA nanocomposite for resisting influenza virus and preparation method and application thereof

CN122953969APending Publication Date: 2026-10-23CHANGCHUN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611030622.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

相较于唾液酸,ConA凭借大分子蛋白天然丰富的结合位点,更易于修饰于纳米材料表面,但目前尚未见关于ConA修饰纳米材料及其在抗流感病毒中的应用的相关报道

Benefits of technology

本发明提供的AuS-ConA复合物以AuS为核心,其表面负载保护剂CTAB,通过共价反应连接上葡萄糖分子,稳固锚定于AuS核心表面实现糖基化修饰;ConA与AuS表面的葡萄糖基通过多重氢键进行特异性的高亲和力结合得到AuS-ConA。相较于现有的唾液酸修饰的纳米材料,ConA凭借大分子蛋白天然丰富的结合位点,使得ConA易于修饰于AuS表面,并保留其细胞膜表面的糖基化合物结合能力。该功能化纳米材料以AuS靶向解构病毒关键蛋白、ConA精准锁定病毒保守糖链实现空间阻断的双重协同机制,有效规避了病毒突变引发的靶点逃逸与耐药性风险,实现高效灭活病毒,将其应用在口罩、防护服、空气净化滤膜等日常防护产品中预防病毒传播,该功能纳米材料具有生物安全性好,靶向作用强,抗病毒能力强等优点。为开发多靶点、广谱且高效的流感防控新产品提供了全新的技术路径。为实现防护物资的抗病毒及自清洁功能,为控制流感病毒的广泛传播提供了一种极具潜力的新材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122953969A_ABST
    Figure CN122953969A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of nanometer functional materials, and specifically discloses an AuS-ConA nanocomposite for resisting influenza virus and a preparation method and application thereof. The nanocomposite takes AuS as a core, loads CTAB on the surface of the core, connects glucose molecules on the core through a covalent reaction, realizes glycosylation modification of the AuS, and then realizes specific combination of the AuS with ConA through multiple hydrogen bonds to prepare the AuS-ConA. The nanocomposite can target and crack disulfide bonds that maintain hemagglutinin on the surface of influenza virus, form a stable gold-sulfur covalent bond, destroy the spatial structure of a virus glycoprotein, make the virus glycoprotein lose receptor recognition and membrane fusion functions, and realize efficient virus inactivation. ConA can competitively combine with the virus glycoprotein on the surface of a host cell to realize high targeting capability and block combination of the virus with a receptor cell. The functional nanomaterial has the advantages of good biological safety, strong targeting effect, strong antiviral capability and the like, and can be applied to daily protection products such as masks, protective clothing, air purification filter membranes and the like to prevent virus transmission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterials technology, and more specifically, relates to an AuS-ConA nanocomposite for anti-influenza virus, its preparation method and application. Background Technology

[0002] Influenza virus, the pathogen that causes influenza, is an RNA virus characterized by high mutation rate, strong infectivity, and rapid spread. It causes seasonal epidemics annually, and some subtypes (such as avian influenza A) can even trigger pandemics, posing a serious threat to individual health and public health. Given the drug resistance caused by the high frequency of influenza virus mutations and the limitations of vaccines, there is an urgent need to develop new broad-spectrum prevention and control measures that can effectively block transmission. The key glycoprotein of influenza virus invading the host, hemagglutinin (HA), is highly dependent on disulfide bonds to maintain its conformation and its surface is enriched with sugar chains such as mannose, providing an ideal target for novel intervention strategies.

[0003] Regarding ligand selection, sialic acid is a natural receptor for influenza virus recognition on receptor cells. However, modifying nanomaterials with sialic acid involves cumbersome and complex procedures, and the connection between sialic acid and nanomaterials (such as CuS and polymers) requires α,2-3 or α,2-6 glycosidic bonds, but existing modification techniques struggle to precisely control the connection type. Most preparation methods (such as enzyme-catalyzed coupling and chemical condensation) tend to produce mixed connection types (α,2-3 and α,2-6 coexisting), leading to decreased adaptability of the material to influenza virus subtypes.

[0004] Cona protein A (ConA) is derived from sword beans ( Canavalia ensiformis ConA, a glycoprotein extracted from seeds, belongs to the lectin family and has wide applications in biomedicine and basic research. Compared to sialic acid, ConA, due to its abundant natural binding sites as a macromolecular protein, is easier to modify onto the surface of nanomaterials. However, there are currently no reports on ConA-modified nanomaterials and their application in anti-influenza virus studies. Therefore, there is an urgent need to develop a multi-target, broad-spectrum, and highly efficient anti-influenza virus nanomaterial to provide technical support for controlling the widespread spread of influenza viruses. Summary of the Invention

[0005] The purpose of this invention is to provide an AuS-ConA nanocomposite for anti-influenza virus, its preparation method, and its application. This nanocomposite uses AuS as the core. First, the amino groups exposed by the surface protectant CTAB covalently bind with the glucose hemiacetal hydroxyl groups that maintain the conformation of natural pyranose, thus anchoring it firmly to the core surface and achieving glycosylation modification. Subsequently, through the specific hydroxyl groups exposed by glucose, it forms multiple hydrogen bonds with concanavalin A for specific high-affinity binding, and finally efficiently cross-links and assembles into a structurally stable functionalized antiviral nanomaterial.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides an AuS-ConA nanocomposite for use against influenza virus, comprising AuS nanoparticles and concanavalin A; the surface of the AuS nanoparticles is loaded with hexadecyltrimethylammonium bromide (CTAB), which is covalently linked to glucose molecules, and the glucose molecules are bonded to ConA through multiple hydrogen bonds.

[0007] A second aspect of the present invention provides an AuS-ConA nanocomposite for use against influenza viruses, comprising the following steps: S1. Dissolve 100 μL of 50 mM HAuCl4 solution and 750 μL of 1 g / mL trisodium citrate solution in 10 mL of water. Heat at 85°C for 15 min. The solution turns wine red, which is the gold seed solution (AuNP). S2. Disperse 400 μL of gold seed solution in 10 mL of water and sonicate. Then, add 100 μL of 50 mM HAuCl4 solution, 20 μL of 10 mM AgNO3 solution, and 100 μL of 100 mM AA solution in sequence. Stir until the solution turns dark blue. After centrifugation and washing twice, collect the precipitate to obtain AuS nanoparticles.

[0008] S3. Prepare a glucose solution, add the original solution of gold nanoparticles to the glucose solution, heat in a water bath at 35°C for 10 hours, centrifuge, take the precipitate, and obtain glycosylated AuS nanoparticles. S4. Glycosylated AuS nanoparticles were added to a ConA solution and reacted at 25°C for 12 h to obtain AuS-ConA nanocomposite.

[0009] In the preferred embodiment, in step S1, the concentration of CTAB in the CTAB solution is 1 mM.

[0010] In the preferred embodiment, step S1, the preparation method of AuS nanoparticles, includes the following steps: 1) Dissolve 100 μL of 50 mM tetrachloroauric acid (HAuCl4) solution and 750 μL of 1 g / mL trisodium citrate solution in 10 mL of water, boil at 85°C for 15 min, and the solution turns wine red, which is the gold seed solution. 2) Disperse 400 μL of gold seed solution in 10 mL of water and sonicate. Then, add 100 μL of 50 mM HAuCl4 solution, 20 μL of 10 mM AgNO3 solution, and 100 μL of 100 mM ascorbic acid (AA) solution in sequence. Stir until the solution turns dark blue. After washing twice by centrifugation, centrifuge again and collect the precipitate to obtain AuS nanoparticles.

[0011] In the preferred embodiment, in step S2, the concentration of glucose in the glucose solution is 2.4 mol / L; the volume ratio of the glucose solution to the original gold nanoparticle solution is 1:2.

[0012] In the preferred embodiment, in step S3, the volume ratio of glycosylated AuS nanoparticles to ConA is 4:1.

[0013] A third aspect of the present invention provides the application of the AuS-ConA nanocomposite for anti-influenza virus prepared by the above method in the preparation of influenza virus protective products, wherein the influenza virus is one or more of H3N2, H3N1, H4N2 and H2N8.

[0014] In a preferred embodiment, the protective product is one or more of the following: a mask, a protective suit, and an air purification filter membrane.

[0015] Beneficial effects of the present invention The AuS-ConA complex provided by this invention uses AuS as its core, with the protective agent CTAB loaded on its surface. Glucose molecules are covalently linked to this core, achieving glycosylation modification. ConA binds specifically and with high affinity to the glucose groups on the AuS surface through multiple hydrogen bonds, resulting in AuS-ConA. Compared to existing sialic acid-modified nanomaterials, ConA, with its naturally abundant binding sites on macromolecular proteins, is easily modified onto the AuS surface while retaining its ability to bind glycosyl compounds to cell membranes. This functionalized nanomaterial employs a dual synergistic mechanism of AuS targeting and deconstructing key viral proteins, and ConA precisely locking onto conserved viral glycan chains to achieve spatial blocking. This effectively avoids the risks of target escape and drug resistance caused by viral mutations, achieving highly efficient viral inactivation. Its application in everyday protective products such as masks, protective clothing, and air purification filters to prevent viral transmission demonstrates advantages such as good biocompatibility, strong targeting, and strong antiviral capabilities. This provides a novel technical pathway for developing multi-target, broad-spectrum, and highly effective influenza prevention and control products. This provides a promising new material for achieving antiviral and self-cleaning functions in protective equipment, and for controlling the widespread spread of influenza viruses. Attached Figure Description

[0016] Figure 1 The UV-Vis absorption spectra of AuNP, AuS, AuS-Glu, and AuS-ConA are shown below; A: Comparison of AuNP and AuS, B: AuS-Glu, C: AuS-ConA.

[0017] Figure 2Transmission electron microscopy (TEM) images of AuS, AuS-Glu, and AuS-ConA nanoparticles and their corresponding particle size distributions; A: AuS, B: AuS-Glu, C: AuS-ConA.

[0018] Figure 3 Zeta potential diagrams for AuS, AuS-Glu, and AuS-ConA nanoparticles.

[0019] Figure 4 The hydration size distribution (DLS) of AuS, AuS-Glu, and AuS-ConA nanoparticles is shown.

[0020] Figure 5 The effects of different concentrations of AuS, AuS-Glu, and AuS-ConA on cell viability.

[0021] Figure 6 The following figures show the results of the H3N2 virus hemagglutination assay: A: Hemagglutination assay for virus titer determination; B: Hemagglutination inhibition assay of different concentration gradients of AuS-ConA; C: Comparison of hemagglutination inhibition assays of AuS, AuS-Glu, and AuS-ConA; D: Hemagglutination inhibition assay of different concentration gradients of AuS; E: Hemagglutination inhibition assay of different concentration gradients of ConA.

[0022] Figure 7 The image shows the results of indirect immunofluorescence assays for AuS, AuS-Glu, and AuS-ConA.

[0023] Figure 8 The application of AuS-ConA in masks: A: Coating effect of AuS-ConA at different concentration gradients on masks; B: Hemagglutination inhibition test of virus after filtration through masks coated with AuS-ConA at different concentration gradients; C: Virus titer detection results after filtration through masks coated with AuS-ConA at different concentration gradients.

[0024] Figure 9 The results are from the broad-spectrum inhibition assay of AuS-ConA. Detailed Implementation

[0025] The present invention will be further described below with reference to specific embodiments. The approximate language used in the following embodiments can be used for quantitative description, indicating that certain variations in quantity are permissible without changing the basic function. The embodiments are intended to illustrate the invention and not to further limit it.

[0026] Example 1

[0027] This embodiment provides the synthesis of AuS.

[0028] 100 μL of 50 mM HAuCl4 solution and 750 μL of 1 g / mL trisodium citrate solution were added to 10 mL of water and heated at 85°C for 15 min to obtain a wine-red gold seed solution (AuNP). 400 μL of the gold seed solution was dispersed in 10 mL of water and sonicated. Then, 100 μL of 50 mM HAuCl4 solution, 20 μL of 10 mM AgNO3 solution, and 100 μL of 100 mM AA solution were added rapidly in sequence. The mixture was gently stirred for about 10 s to 3 min until the solution turned deep blue. After two cycles of centrifugation (8000 r / min), washing, and finally centrifugation, the precipitate was collected, which is the AuS nanoparticle.

[0029] Characterization analysis of AuS nanoparticles was performed. The UV-Vis spectra of AuNP and AuS showed a significant change in the absorption peaks after the conversion of AuNP to AuS. Figure 1 A); TEM images and particle size distribution maps of AuS show that AuS exhibits a uniformly distributed, sharply branched morphology, with an average physical particle size of 45±20 nm. Figure 2 A); The surface Zeta potential of AuS is 34mV ( Figure 3 The average hydrated particle size determined by DLS was 50 nm. Figure 4 ).

[0030] Example 2

[0031] This embodiment provides the synthesis of AuS-Glu.

[0032] First, a seed crystal method was used to prepare the gold nanoparticle stock solution. The AuS nanoparticles prepared in Example 1 were dispersed in 10 mL of 1 mM CTAB solution to obtain the AuS nanoparticle stock solution. Then, 1 mL of freshly prepared 2.4 mol / L glucose solution was added to 2 mL of the prepared AuS nanoparticle stock solution, gently shaken for 5 seconds to mix, and placed in a 35°C water bath for 10 hours to react. After centrifugation at 8000 r / min, the precipitate was collected to obtain glycosylated gold nanoparticles (AuS-Glu).

[0033] The AuS-Glu nanoparticles were characterized. The characterization results showed that after coating the AuS surface with glucose, the absorption peak position did not exhibit a significant blue shift. Figure 1 B), Transmission electron microscopy ( Figure 2 B) shows that the nanoparticle morphology remains stable, with an average physical particle size of 115±20 nm. Compared to AuS, due to the presence of hydroxyl groups (-OH) on the glucose surface forming a tightly attached hydration layer, the hydrated particle size of AuS-Glu significantly increases to 105 nm. Figure 4 At the same time, the Zeta potential changed from positive to negative and dropped to -2mV ( Figure 3This confirms the successful assembly of the target group on the surface of the nanoparticles.

[0034] Example 3

[0035] This embodiment provides the synthesis of AuS-ConA.

[0036] Prepare a ConA stock solution with a final ConA concentration of 2 mg / mL using 25 mg of concanavalin A (ConA) in phosphate-buffered saline (PBS) at pH 7.4. When needed, dilute the ConA solution to the required concentration with PBS. Prepare an AuS-Glu solution with a final AuS-Glu concentration of 25 mg / mL using the AuS-Glu prepared in Example 2.

[0037] The ConA stock solution was diluted with PBS to prepare a 60 mM ConA solution. 500 μL of the ConA solution was added to a 5 mL centrifuge tube, followed by 2 mL of the prepared AuS-Glu solution. The mixture was reacted at room temperature (25 °C) for 12 h to obtain AuS-ConA nanoparticles.

[0038] Characterization of AuS-ConA nanoparticles. Ultraviolet-Vis spectroscopy analysis (UV-Vis spectroscopy) Figure 1 C) indicates that a new absorption peak appears and the absorbance decreases after coupling with ConA, which is due to the cross-linking and aggregation precipitation between particles; transmission electron microscopy (TEM) Figure 2 C) shows that its average physical particle size has decreased to 55±15 nm; Zeta potential ( Figure 3 The voltage continued to decrease to -20 mV. Simultaneously, due to the specific binding of ConA to sugar molecules, the sugar chains compressed, hydrophilic sites were shielded, and bound water was released, causing the hydrated particle size to drop back to 68 nm. Figure 4 The continuous and regular changes in these surface potentials and hydrated particle sizes further verify the specific binding of ConA on the AuS-Glu surface and the successful preparation of AuS-ConA.

[0039] Example 4

[0040] This embodiment demonstrates the cytotoxic effect of AuS-ConA on MDCK cells.

[0041] The in vitro toxicity of AuS, AuS-Glu, and AuS-ConA prepared in Examples 1-3 to MDCK cells was evaluated using the MTT assay. Figure 5 As shown, the inhibitory effects of the three nanoparticles on the proliferation of MDCK cells were all significantly dose-dependent; when the drug concentration reached 12 μg / mL, the relative survival rate of cells in each group remained above 50%. The results indicate that the AuS-ConA nanocomposite material exhibits good biocompatibility and cell tolerance within the concentration range of 0–12 μg / mL.

[0042] Example 5

[0043] This embodiment provides experiments on the hemagglutination and hemagglutination inhibition of erythrocytes by influenza virus H3N2.

[0044] To systematically evaluate the specific binding and inhibitory ability of the nanocomposite material provided by the present invention against H3N2 influenza virus, in vitro erythrocyte agglutination and hemagglutination inhibition experiments were carried out using AuS, AuS-Glu and AuS-ConA prepared in Examples 1-3.

[0045] First, the hemagglutination activity of the working virus was determined using a standard hemagglutination assay, such as... Figure 6 As shown in Figure A, 50 μL of physiological saline was added to each well of the hemagglutination plate. 50 μL of H3N2 virus solution was added to column 1, and serial dilutions were performed two-fold up to column 11. Column 12 was reserved as a physiological saline blank control. Subsequently, 50 μL of 1% chicken erythrocyte suspension was added to each well, vortexed for 1 min, and allowed to stand for 30 min before observing the hemagglutination results. Complete cross-linking and agglutination of erythrocytes was still induced at a 1:64 dilution, confirming the good activity of the virus and thus accurately determining the standard working concentration for subsequent experiments. Subsequently, to verify the basic antiviral activity of the material, it was diluted and administered the drug according to the above dilution method. Figure 6 As shown in Figure C, the AuS, AuS-Glu, and AuS-ConA administration groups all formed tight erythrocyte precipitation points, which clearly indicates that all three can effectively bind to the virus and block hemagglutinin, successfully blocking the erythrocyte agglutination reaction.

[0046] To further confirm the structural advantages and synergistic mechanism of the whole-drug composite material (AuS-ConA) of this invention, a concentration gradient comparative analysis of each component was conducted. The results showed that the antiviral efficacy of each individual component was relatively limited, as indicated below. Figure 6 As shown in B, 6D, and 6E.

[0047] like Figure 6 As shown in D, unmodified AuS alone requires a concentration of 48 μg / mL to produce complete hemagglutination inhibition; Figure 6 As shown in E, free concanavalin A monomers only exhibit a weak inhibitory trend at extremely high milligram levels (56–102 mg / mL). However, as Figure 6As shown in Figure B, when ConA was successfully modified onto the AuS surface to form a fully-drug composite material, its efficacy was greatly enhanced, completely blocking virus-mediated erythrocyte aggregation at a concentration as low as 12 μg / mL. These results comprehensively confirm that the interaction between ConA and AuS is not a simple physical superposition, but rather a remarkably significant synergistic effect. The modification with concanavalin A endows the nanosystem with highly efficient targeted recognition of influenza viruses, significantly reducing the minimum effective inhibitory concentration and demonstrating excellent in vitro antiviral potential.

[0048] Example 6

[0049] This example provides an indirect immunofluorescence experiment.

[0050] This experiment evaluated the antiviral effects of the AuS, AuS-Glu, and AuS-ConA nanoparticles prepared in Examples 1-3 using immunofluorescence. MDCK cells were cultured into monolayers in 48-well plates and then subjected to 100 TCID50. 50 Cells were infected with H3N2 virus by incubation for 1 hour. Subsequently, they were treated with 12 μg / mL AuS, AuS-Glu, and AuS-ConA nanoparticles prepared in DMEM containing TPCK trypsin for 24 hours, respectively. A blank control group, a virus control group, and an oseltamivir (12 μg / mL) positive control group were also established. After washing, cells were fixed with 4% paraformaldehyde for 30 minutes, permeabilized with methanol at 4°C for 15 minutes, and blocked with 5% BSA for 1 hour. Then, mouse anti-H3N2 NP monoclonal antibody was added and incubated overnight at 4°C; after washing, Alexa Fluor 488 fluorescent secondary antibody was added and incubated in the dark for 1 hour. Finally, nuclear staining was performed with DAPI for 10 minutes.

[0051] The results are as follows Figure 7 As shown, the blank control group (PBS) showed no green fluorescence signal, while the virus model group (H3N2) exhibited a large area of ​​strong green light, indicating that the virus had successfully infected and was expressed in large quantities within the cells. Comparative experiments showed that treatment with AuS nanoparticles without specific ligand modification or AuS-Glu nanoparticles grafted only with glucose still resulted in strong green fluorescence within the cells, indicating that they could not effectively prevent viral infection. In contrast, the green fluorescence signal of the AuS-ConA nanoparticle treatment group described in this invention was greatly weakened, with only extremely weak fluorescence remaining, and its inhibitory effect was essentially equivalent to that of the positive control drug oseltamivir (OTV) group. These results fully confirm that surface loading with concanavalin A (ConA) is a key prerequisite for the antiviral activity of these nanoparticles, and that AuS-ConA nanoparticles can extremely effectively block the infection and proliferation of H3N2 influenza virus within host cells.

[0052] Example 7

[0053] This example demonstrates the application of AuS-ConA in face masks.

[0054] AuS-ConA solutions at concentrations of 0.6, 1.2, and 2.4 mg / mL were applied to the outermost layer of a three-layer face mask at a rate of 1 mL / cm² and dried in a cool airflow at room temperature for 30 min. An equal volume of H3N2 influenza virus was then inoculated into the treated area and incubated for 1 h. The treated area fabric was cut and placed in a centrifuge tube containing 500 μL PBS, and the virus solution was collected after elution. Using the untreated area as a blank control, the virus titer was determined by a hemagglutination inhibition test. Results are as follows: Figure 8 The material exhibits significant and dose-dependent antiviral activity. The 1.2 mg / mL treatment group showed a marked inhibitory effect on the virus; at a concentration of 2.4 mg / mL, the virus was almost completely inhibited, effectively demonstrating the excellent antiviral performance of the AuS-ConA material when applied to masks.

[0055] Example 8

[0056] This example provides a broad-spectrum inhibition experiment of AuS-ConA.

[0057] MDCK cells were seeded at 8 × 10³ / well in 96-well plates and cultured for 24 h. 100 μL of water was then added to each well. Cells were infected with H1N1, H3N2, H2N8, H4N2, and H3N1 viruses for 2 hours, washed with PBS, and then treated with AuS-ConA prepared in Example 3 for 2 hours. The culture medium was then replaced and the cells were cultured for another 48 hours. Cell viability at 490 nm was detected by the MTT assay. Results are as follows: Figure 9 As shown, AuS-ConA exhibits significant protective effects against H1N1 and H3N2, with cell survival rates exceeding 90%; the survival rates against H3N1, H4N2, and H2N8 are approximately 88%, 80%, and 80%, respectively. Experiments confirm that AuS-ConA possesses excellent broad-spectrum antiviral effects against multiple influenza subtypes.

[0058] The AuS-ConA complex for anti-influenza virus provided by this invention uses AuS as the core. In solution, glucose molecules maintain the natural pyranose spatial conformation. Its hemiacetal hydroxyl groups covalently bind to the amino groups exposed by the AuS surface protectant cetyltrimethylammonium bromide (CTAB), thereby firmly anchoring to the AuS surface and achieving glycosylation modification. The anchored glucose C-3 / C-4 and C-6 hydroxyl groups are exposed to the outside, and then bind to ConA with specific high affinity through multiple hydrogen bonds, forming a stable dual synergistic complex (AuS-ConA) through efficient cross-linking.

[0059] Among them, AuS utilizes gold's high affinity for sulfur to target and cleave the disulfide bonds of hemagglutinin on the surface of the virus, forming a stable gold-sulfur (Au-S) covalent bond. This irreversible process disrupts the spatial structure of the viral glycoprotein, causing it to lose its receptor recognition and membrane fusion functions, thereby achieving highly efficient virus inactivation. The material-loaded ConA can competitively bind to the glycoproteins on the surface of the influenza virus with host cells, achieving high targeting capability. It can block the binding of the virus to receptor cells, enabling its use in everyday protective products such as masks, protective clothing, and air purification filters to prevent virus transmission. This functional nanomaterial has advantages such as good biocompatibility, strong targeting effect, and strong antiviral capability.

[0060] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. An AuS-ConA nanocomposite for anti-influenza virus, characterized in that, It includes AuS nanoparticles and concanavalin A; the surface of the AuS nanoparticles is loaded with CTAB, which is linked to glucose molecules through a covalent reaction, and the glucose molecules are linked to ConA through multiple hydrogen bonds.

2. An AuS-ConA nanocomposite for anti-influenza virus, characterized in that, Includes the following steps: S1. AuS nanoparticles are dispersed in CTAB solution to obtain gold nanoparticle stock solution (AuNP). S2. Prepare a glucose solution, add the original solution of gold nanoparticles to the glucose solution, heat in a water bath at 35°C for 10 hours, centrifuge, take the precipitate, and obtain glycosylated AuS nanoparticles. S3. Glycosylated AuS nanoparticles were added to a ConA solution and reacted at 25°C for 12 h to obtain AuS-ConA nanocomposite.

3. The AuS-ConA nanocomposite for anti-influenza virus according to claim 2, characterized in that, In step S1, the concentration of CTAB in the CTAB solution is 1 mM.

4. The AuS-ConA nanocomposite for anti-influenza virus according to claim 2, characterized in that, In step S1, the preparation method of the AuS nanoparticles includes the following steps: 1) Dissolve 100 μL of 50 mM HAuCl4 solution and 750 μL of 1 g / mL trisodium citrate solution in 10 mL of water, heat at 85°C for 15 min, the solution turns wine red, which is the gold seed solution; 2) Disperse 400 μL of gold seed solution in 10 mL of water and sonicate. Then, add 100 μL of 50 mM HAuCl4 solution, 20 μL of 10 mM AgNO3 solution, and 100 μL of 100 mM AA solution in sequence. Stir until the solution turns dark blue. After washing twice by centrifugation, centrifuge again and collect the precipitate to obtain AuS nanoparticles.

5. The AuS-ConA nanocomposite for anti-influenza virus according to claim 2, characterized in that, In step S2, the concentration of glucose in the glucose solution is 2.4 mol / L; the volume ratio of the glucose solution to the original gold nanoparticle solution is 1:

2.

6. The AuS-ConA nanocomposite for anti-influenza virus according to claim 2, characterized in that, In step S3, the volume ratio of glycosylated AuS nanoparticles to ConA is 4:

1.

7. The application of an AuS-ConA nanocomposite for anti-influenza virus prepared by the method according to any one of claims 2 to 6 in the preparation of influenza virus protective products, characterized in that, The influenza virus is one or more of H3N2, H3N1, H4N2 and H2N8.

8. The application of the AuS-ConA nanocomposite for anti-influenza virus according to claim 7 in the preparation of influenza virus protective products, characterized in that, The protective products are one or more of the following: masks, protective clothing, and air purification filter membranes.